Optimization of Valorization of Chicken MDCM to Produce Soluble Protein and Collagen Peptides - Nora Pap; Sari Mäkinen; Ulla Moilanen; Marjatta Vahvaselkä; Jyri Maunuksela; Maritta Kymäläinen; Anne Pihlanto (Applied Sciences, 2022)
This study aimed to utilize enzymatic treatment and pressurized hot water extraction (PHWE) to recover soluble food-grade protein and collagen peptides from mechanically deboned chicken meat (MDCM), a side-stream from the meat industry. Food-grade enzyme blends Ermitase 1 and Ermitase 2 were used to fractionate the mechanically deboned meat into fat, soluble protein, and solids. Response surface methodology was utilized to optimize treatments to maximize the protein yield. At the optimum conditions (hydrolysis time 240 min, E:S 0.27%, and a hydromodule 1 L/kg), the enzymatic treatment produced high protein yield, approximately 90%. The protein hydrolysates showed a good solubility index, but weak gelling properties. The PHWE of the bones resulted in a high nitrogen yield, approximately 87%, at the optimum conditions of 190 °C and 83 min. Peptides in the bone extract were in the range of 0.5–13.7 kDa. Overall, our study highlights the importance of response surface methodology to optimize parameters for mechanically deboned chicken meat enzymatic and PHWE treatments to achieve high yields of protein for food applications and low-molecular-weight collagen peptides for cosmetic applications. The crucial role of protein and peptide prices was observed in preliminary profitability analysis.